Optical fiber sensors for static and dynamic health monitoring of civil engineering infrastructures: Abode wall case study - Antunes, P.
Nowadays, structural health monitoring is a fundamental tool to control the civil infrastructures lifetime. Raw earth masonry structures (as adobe, rammed earth, among other techniques) were very common in many regions of the World. With the introduction of reinforced concrete structures in the construction industry, the adoption of traditional masonry systems, and adobe in particular, rapidly declined. However, an important number of the adobe buildings in the world are of cultural, historical and architectural recognized value, presently, about 30% of the World population lives in raw earth buildings. In this paper, the monitoring of an adobe masonry structure with an optical fiber accelerometer and a network of thirteen multiplexed displacement sensors is reported. The measurements were made during a destructive test on a full-scale wall. The measured values showed a decrease of 48% in the structure first natural frequency value, between the initial situation and after the cyclic test. Our results demonstrated that optical sensors can be useful in static and dynamic monitoring of large raw earth masonry structures.